2012
DOI: 10.1038/ni.2225
|View full text |Cite
|
Sign up to set email alerts
|

A CD74-dependent MHC class I endolysosomal cross-presentation pathway

Abstract: Immune responses are initiated and primed by dendritic cells (DCs) that cross-present exogenous antigen. The CD74 (invariant chain) chaperone protein is thought to exclusively promote DC priming in the context of MHC class II. However, we demonstrate herein a CD74-dependent MHC class I cross-presentation pathway in DCs that plays a major role in the generation of MHC class I restricted, cytolytic T lymphocyte (CTL) responses against viral protein- and cell-associated antigens. CD74 associates with MHC class I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 51 publications
3
105
1
Order By: Relevance
“…Three groups reported that Ags delivered via the mannose receptor were routed into early endosomes resulting in more efficient cross-presentation. 9,44,46 In contrast, we observed that mannose NPs were not routed into early but rather into acidic endosomes, which did not interfere with cross-presentation of the epitope HER2/neu 369-377 . Actually, our studies showed that some degree of acidification was crucial for the generation of the peptide HER2/neu 369-377 , which is compatible with antigen processing by cathepsins that are activated at low pH.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Three groups reported that Ags delivered via the mannose receptor were routed into early endosomes resulting in more efficient cross-presentation. 9,44,46 In contrast, we observed that mannose NPs were not routed into early but rather into acidic endosomes, which did not interfere with cross-presentation of the epitope HER2/neu 369-377 . Actually, our studies showed that some degree of acidification was crucial for the generation of the peptide HER2/neu 369-377 , which is compatible with antigen processing by cathepsins that are activated at low pH.…”
Section: Discussioncontrasting
confidence: 45%
“…According to some reports, antigen for cross-presentation needed to be routed into non-acidified compartments and acidification prevented or decreased cross-presentation. 44,45 We found efficient cross-presentation in both situations. Three groups reported that Ags delivered via the mannose receptor were routed into early endosomes resulting in more efficient cross-presentation.…”
Section: Discussionmentioning
confidence: 69%
“…by guest www.bloodjournal.org From early endosomes, 33,40 late endosomes or endo/lysosomes. [41][42][43] These phagosomes contain MHCI loading complex components. 36,37,40,44,45 To clarify mechanisms involved in BDCA-3 ϩ DC crosspresentation, we tested the involvement of endosomal and proteasomal processing, analogous to experiments described in Figure 2.…”
Section: Differential Antigen Uptake Does Not Explain Increased Crossmentioning
confidence: 99%
“…Powis (2006) reported that the CLIP region is directly involved in the association of Ii with MHC class I molecules, and that this can result in the inclusion of Ii in the MHC class I peptide-loading complex. Recent research showed that Ii associated with MHC class I in the endoplasmic reticulum of DCs and mediated trafficking of MHC class I to endolysosomal compartments for loading with exogenous peptides (Basha et al, 2012).…”
Section: Introductionmentioning
confidence: 99%